Quantum mechanics - Auletta, Gennaro, 1957-, author; Fortunato, Mauro, author; Parisi, Giorgio, author (Cambridge, U.K. ; New York : Cambridge University Press, 2013)
Includes bibliographical references (p. [674]-709) and indexes